Analysis of the Relationship Between Peer Bullying and Boredom in Schools in Serbia: PISA 2022 - Đukić, Daliborka (Studies in Teaching and Education, 2025)
This paper examines the relationship between forms of peer bullying and the presence of boredom in the school environment in the Republic of Serbia, based on data obtained from the PISA 2022 survey. The consequences of experienced peer bullying are highly negative and long-lasting, affecting all aspects of students’ lives, including academic, psychological, health, and social domains. Therefore, it is crucial to explore the factors associated with bullying in order to mitigate and prevent all forms of aggression in schools, including peer violence. Recent research has shown a positive association between the feeling of boredom and peer bullying. This study utilizes data from the PISA survey conducted in the Republic of Serbia, with a sample of 6,413 students from 181 schools. Two groups of statements were selected from the student questionnaire: one measuring the frequency of bullying and the other assessing the feeling of boredom. Through factor analysis, two factors of bullying were identified: relational bullying and physical bullying combined with verbal abuse. Similarly, two factors related to boredom were identified: distraction and disengagement from tasks and interests. Further analysis revealed a significant positive correlation between these factors, particularly between boredom and physical/verbal bullying. These findings suggest that the educational system must recognize students exhibiting higher levels of boredom, as they are at increased risk of displaying aggression and engaging in peer bullying. Additionally, it is advisable to integrate and apply various methods and approaches that have proven effective in reducing boredom among students into educational strategies.